PEMBATALAN HAK ATAS TANAH OBJEK NOMINEE AGREEMENT (Lex Jurnalica, 2021)
Property rights are defined as rights that are hereditary, strongest and most fulfilled. Article 21 of the Basic Agrarian Law stipulates that only Indonesian citizens can own property rights. This prevents foreigners from acquiring land with property rights. Therefore, they use the Nominee Agreement which can indirectly help them obtain ownership rights in Indonesia. This study is intended to analyze the validity of the issued Land Rights Certificates on land obtained under the Nominee Agreement and what the Indonesian government should do about the problem. This research is a normative legal research that focuses on examining existing laws and legal concepts related to these problems. Regarding the problems in this study, not only the nominee agreement was canceled but also the land ownership rights obtained with the nominee agreement must also be canceled. Keywords: land law, nominee agreement, right of ownership, land rights